EFEKTIVITAS KOMBINASI FISIOTERAPI DADA DAN SUCTION TERHADAP PENURUNAN PRODUKSI SPUTUM PADA PASIEN GAGAL NAFAS DI RUANG ICU RUMAH SAKIT SWASTA 2024: CASE REPORT: Effectiveness of a Combination of Chest Physiotherapy and Suction on Reducing Sputum Production in Patients with Respiratory Failure in the ICU Room of a Private Hospital 2024: Case Report - Afrianus Afrianus; Diah Pujiastuti; Margaretha Rina Anjarwati (Forind Press, 2024)
Respiratory failure is a failure in the gas exchange function between oxygen and carbon dioxide which can cause decreased consciousness. One of the complications of decreased consciousness that is often encountered is sputum retention. The intervention carried out was chest physiotherapy combined with suction. Based on a preliminary study, it was found that 24 (80%) experienced respiratory failure. To reduce sputum production in patients with respiratory failure with chest physiotherapy intervention combined with suction in the ICU of a private hospital. The research method used in this research is a case report by conducting intervention observations and also airway clearance research with 1 respondent. After chest physiotherapy combined with suction, the results showed an increase in oxygen saturation from 88% to 99% and sputum production decreased from ± 10 cc to ± 7 cc. After chest physiotherapy combined with suction for 3 days, significant results were obtained, namely an increase in oxygen saturation and also a decrease in sputum production. ICU nurses are expected to be able to apply chest physiotherapy combined with suction to reduce sputum production in patients with respiratory failure in the ICU by paying attention to vital signs. Intervention is carried out once a day.